Numerical Parametric Analysis of PW INKA Pistol - Przemysław BADUROWICZ (Numeryczna analiza parametryczna pistoletu PW INKA, 2023)
The paper describes the results of the parametric analysis obtained using the multibody systems. Numerical analysis allows checking different variants of the weapon without the need of building a lot of experimental models. As a part of the analysis, the impact of the slide mass, the recoil spring stiffness, the friction coefficients, the propellant gas pressure, and the force of bullet engraving the barrel on the kinematic characteristics of the weapon were checked. The extreme values of the slide mass and the recoil spring stiffness were selected, after crossing them, the correct operation of the weapon would not be possible. The operation of the pistol was checked for its multiple variants, taking into account its lubrication, lack of lubrication, and lack of friction by appropriate selection of the friction coefficients. The propellant gas pressure variants were selected to reflect the pressure in the barrel during shoot using ammunition manufactured according to different standards and of different quality. The models, taking into account the force of bullet engraving the barrel and those ignoring such force, were developed to check their impact on the kinematic characteristics of a short recoil operated weapon.
Keywords: Analiza kinematyczna pistoletu